1989
DOI: 10.1159/000185581
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Renal Tubular Effects in Relation to Urine Cadmium Levels

Abstract: In this study the urine activities of two brush border membrane enzymes, alanine aminopeptidase (AAP) and γ-glutamyltranspeptidase (GGT), and the lysosomal enzyme N-acetyl-β-D-glucosaminidase (NAG) were measured in men exposed to cadmium to investigate chronic renal toxicity. The subjects consist of a group with urine cadmium levels < 2.0 μg/l and a group with higher cadmium levels (urine cadmium > 2.0 μg/l) with past or present occupational exposure to cadmium. The mean NAG value corrected for creatinine in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…In studies of health effects caused by exposure to cadmium, the urinary cadmium concentration is often used as an indicator of internal dose. Reports on cadmium levels of workers and animals have shown a close relationship between urinary cadmium excretion and the total body burden of cadmium (23)(24)(25)(26)(27). We found that urinary cadmium increased with the increasing lifetime cadmium intake among inhabitants of the general environment (10).…”
Section: Discussionmentioning
confidence: 54%
“…In studies of health effects caused by exposure to cadmium, the urinary cadmium concentration is often used as an indicator of internal dose. Reports on cadmium levels of workers and animals have shown a close relationship between urinary cadmium excretion and the total body burden of cadmium (23)(24)(25)(26)(27). We found that urinary cadmium increased with the increasing lifetime cadmium intake among inhabitants of the general environment (10).…”
Section: Discussionmentioning
confidence: 54%
“…An association between AAP and urinary cadmium was previously observed in studies of individuals with high occupational exposures (7,11), and NAG has been used as a marker of cadmium nephrotoxicity in several occupational and environmental studies (7,(10)(11)(12)33,34).…”
Section: Discussionmentioning
confidence: 77%
“…Elevations in enzymes primarily of renal tubular origin, such as N-acetyl-β-Dglucosaminidase (NAG) and alanine aminopeptidase (AAP), have been observed at occupational cadmium exposures of 3.7-6.3 µg urinary cadmium/g creatinine (2,4,7). Increases in these enzymes have been associated with chemical-induced renal tubular damage (8,9) Most studies of cadmium-induced renal effects using these and other biomarkers have been conducted among individuals with occupational or high environmental exposures (4,7,(10)(11)(12)(13)(14)(15)(16). Results of a national health survey indicate that the geometric mean value (and 95th percentile) for urinary cadmium among the U.S. general population age 6 years or older is approximately 0.27 (1.48) µg/g creatinine (17), but little information is available on renal effects that may occur in people with urinary cadmium levels < 2 µg/g.…”
mentioning
confidence: 99%
“…[33][34][35] In either of our surveys, abnormal levels of NAGA or AAP (defined by the arithmetic mean in the unexposed plus two standard deviations) were associated only with urine cadmium levels greater than 10 ug/g creatinine.…”
Section: B Medicalmentioning
confidence: 61%